Aristotle on the indetermination of accidental causes and chance - Rossi, Gabriela (2018)
This article offers an interpretation of Aristotle’s tenet that chance and accidental causes are indeterminate. According to one existing reading, the predicate ‘indeterminate’ is said of the effect of chance (and of accidental causes), meaning ‘causally indeterminate.’ Another reading claims instead that the predicate ‘indeterminate’ is said of the cause of a chance event, meaning something close to ‘potentially infinite in number.’ For my part, I contend that the predicate ‘indeterminate,’ when applied to Aristotle’s concept of accidental cause and to chance, is best understood as a second-order predicate. More precisely, Aristotle uses ‘indeterminate’ to qualify a certain type of causal relation, rather than to indicate a quality of the causal power or of the effect. As a preparatory step in my argument, I contend that ‘accidental’ and ‘per se’ are also best understood as second-order predicates of ‘cause,’ and as a corollary of my main thesis I offer an interpretation of how chance involves an infinite number of possible causes.